Contradições na atividade de trabalho das professoras dos anos iniciais em uma escola do Estado do Tocantins - Luciana Pereira de Sousa (2020)
This study deals with the complexity of the relationships that constitute the work of teachers in the first years of elementary, in the context of globalized capitalist society. Specifically, it investigates the learning processes of four teacher, when they need to deal with the demands of the Work Activity in a community school, in partnership with the state education network of Tocantins. The research has a qualitative approach based on the perspective of Ethnography in Education, using participative observation in a school during one semester. The research empirical material is composed by class registries in 4th and 5th grade classes, planning meetings, and interviews with the participant teachers. The analyses were done through the perspective of expansive learning under the theoretical scope of Cultural-Historic Activity Theory. Under these theoretical lenses, it was possible to broaden the view on the subjects-in-action (teachers) guided to school teaching and connected to the historic movements in education through the educational policies implemented in the state. We structured an unity of analysis “Activity system on the teachers’ work” and, through different movements, positioned the analysis lenses either on the micro level of the classroom or the macro level of work relations of those teachers with the state educational system, showing the tensions and the contradictions in the Activity System. Faced by the contradiction in the Activity, the teachers live dilemmas and conflicts that oscillate in opposite fronts of the educational context: teaching for a type of learning that is seen as human development for the children versus teaching to fulfill the goals of efficiency and excellence of the educational system indicators. The analysis reveals that, when facing the tensions, the teachers provoke constant restructuring, changing teachers’ everyday life and creating work overload. On the other hand, the teachers show some resistance to the impositions of neoliberal reproduction model, showing an action empowerment when they are collectively organized and create alternative ways of teaching that are not hierarchized by the system. The way teachers face Activity contradictions show a dialectic between structure versus agency, as they try to find, by themselves, ways to deal with and break away from the ways their works are regulated by the educational system. The study reveals how the discourse of the Organisation for Economic Co-operation and Development reproduced withing the educational system of Tocantins reinforces the emphasis of the subject Mathematics to reach good evaluation indexes and the distinction of the school within the education system. This discourse also regulates teachers’ work for a type of training that attends the demands of the market, connecting them to a precarious professional life. However, they persist in their work towards an education that aims learning as a process of children’s human development.